Acute Pain Management in Vatakaphaja Gridhrasi - Swathi N; Misriya K H; Ananta S Desai (AYUSHDHARA, 2024)
Gridhrasi is one of the Vataja Nanatmaja Vyadhi in which the vitiated Vata afflicts the Kandara and Sira of lower limb leading to Stambha, Ruk, Toda along with Spandana starting from Kati Pradesha to Prustha, Janu, Jangha and Pada of either one side or both side of the lower limbs. Due to similarities in the clinical presentation, it can be studied under the spectrum of Intervertebral Disc Prolapse of lumbar spine. It is a condition affecting the spine in which the annulus fibrosus is damaged enabling nucleus pulposus to herniate, due to which there will be compression of Spinal Cord or the exiting nerve roots causing severe pain in the low back radiating to lower limbs. The incidence of Herniated disc is about 5 to 20 cases per 1000 adults annually and is most common in male patients when compared with female. In this case a male patient of age 36 suffering with acute pain in the low back region was effectively managed by Nadi Sweda followed by dry cupping for 7 days, followed by Patra Pinda Sweda for 7 days. The study shows significant relief in the pain and remarkable improvement in the range of movement of lumbar spine.